2020
DOI: 10.1001/jamanetworkopen.2020.25109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Tumor Mutational Burden and Association With Survival in Patients With Less Common Solid Tumors

Abstract: IMPORTANCE Tumor mutational burden (TMB) is a potential biomarker associated with response to immune checkpoint inhibitor therapies. The prognostic value associated with TMB in the absence of immunotherapy is uncertain. OBJECTIVE To assess the prevalence of high TMB (TMB-H) and its association with overall survival (OS) among patients not treated with immunotherapy with the same 10 tumor types from the KEYNOTE-158 study. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study evaluated the prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 32 publications
5
65
3
Order By: Relevance
“…The overall prevalence of TMB-H in this study was 15.5%, similar to that reported in the KEYNOTE-158 study. Also, in our study, NETs and biliary tumors had much higher TMB-H rates than that in the KEYNOTE-158 study (43.8% vs 29.3%, 25.5% vs 4.0%, respectively) ( 20 , 50 ). Given the high prevalence of TMB-H status in rare tumors, the effect of TMB on immunotherapy response in rare tumors deserves further exploration.…”
Section: Discussioncontrasting
confidence: 55%
“…The overall prevalence of TMB-H in this study was 15.5%, similar to that reported in the KEYNOTE-158 study. Also, in our study, NETs and biliary tumors had much higher TMB-H rates than that in the KEYNOTE-158 study (43.8% vs 29.3%, 25.5% vs 4.0%, respectively) ( 20 , 50 ). Given the high prevalence of TMB-H status in rare tumors, the effect of TMB on immunotherapy response in rare tumors deserves further exploration.…”
Section: Discussioncontrasting
confidence: 55%
“…Cancer in adult humans typically has dozens to hundreds of mutations per case, while pediatric cancers usually have far fewer mutations per case ( 58 ). A commonly employed metric for describing the frequency of mutations in a given cancer case is the tumor mutational burden (TMB), represented by the number of mutations per Mb (megabase, i.e., one million DNA bases) ( 81 ). A recent review of over 100,000 human cancer cases across more than 500 cancer types revealed a wide TMB spectrum, ranging from 0 to over 1,000 mutations/Mb, with a median of 3.6 mutations/Mb and increasing with patient age ( 82 ).…”
Section: Fundamentals Of Cancer Genomicsmentioning
confidence: 99%
“…Theoretically, a higher TMB should therefore increase the likelihood for tumor neo-antigen production and as such the probability for immune recognition and tumor cell killing [ 147 ]. Even though MPM is considered to have a low TMB [ 48 , 148 , 149 ], TMB has been assessed is some available studies of checkpoint inhibitors.…”
Section: Outstanding Issues and Other Therapeutic Considerationsmentioning
confidence: 99%